Transferability of interatomic potentials for silicene - Maździarz, Marcin (Beilstein Journal of Nanotechnology, 2023)
The ability of various interatomic potentials to reproduce the properties of silicene, that is, 2D single-layer silicon, polymorphs was examined. Structural and mechanical properties of flat, low-buckled, trigonal dumbbell, honeycomb dumbbell, and large honeycomb dumbbell silicene phases, were obtained using density functional theory and molecular statics calculations with Tersoff, MEAM, Stillinger–Weber, EDIP, ReaxFF, COMB, and machine-learning-based interatomic potentials. A quantitative systematic comparison and a discussion of the results obtained are reported.
Keywords: 2D materials; DFT; force fields; interatomic potentials; mechanical properties; silicene